About the origin and environment of Panthera spelaea (Goldfuss, 1810) - Alain Argant; Jacqueline Argant (Earth History and Biodiversity)
Current phylogenies focus on the phyletic relationships between sister taxa of species, but none point to an ancestral species that gave rise to Panthera spelaea. The knowledge of its origins is progressing, but the question remains of whether this ancestral form is Eurasian or African, and at what period in the Plio-Pleistocene the divergence may have taken place. In this collective work on Panthera spelaea, the Eurasian species par excellence, the question of whether Panthera gombaszogensis may have evolved into Panthera spelaea is once again raised and examined in the light of current data. In the absence of decisive new data, it may be useful to reverse the problem and start from hypotheses. The environment plays a fundamental role in the evolution of species, and the hypothesis adopted must necessarily take this into account. Panthera gombaszogensis morphology, extensive distribution, and great adaptability to a variety of ecosystems suggest that it is a potential Eurasian ancestor of the cave lion. Chronology, whose role remains decisive, makes this possible.